Kinetic Modeling for the “One-Pot” Hydrogenolysis of Cellulose to Glycols over Ru@Fe3O4/Polymer Catalyst - Oleg Manaenkov; Yuriy Kosivtsov; Valentin Sapunov; Olga Kislitsa; Mikhail Sulman; Alexey Bykov; Alexander Sidorov; Valentina Matveeva (Reactions, 2021)
Despite numerous works devoted to the cellulose hydrogenolysis process, only some of them describe reaction kinetics. This is explained by the complexity of the process and the simultaneous behavior of different reactions. In this work, we present the results of the kinetic study of glucose hydrogenolysis into ethylene- and propylene glycols in the presence of Ru@Fe3O4/HPS catalyst as a part of the process of catalytic conversion of cellulose into glycols. The structure of the Ru-containing magnetically separable Ru@Fe3O4/HPS catalysts supported on the polymeric matrix of hypercrosslinked polystyrene was studied to propose the reaction scheme. As a result of this study, a formal description of the glucose hydrogenolysis process into glycols was performed. Based on the data obtained, the mathematical model of the glucose hydrogenolysis kinetics in the presence of Ru@Fe3O4/HPS was developed and the parameter estimation was carried out. The synthesized catalyst was found to be characterized by the enhanced magnetic properties and higher catalytic activity in comparison with previously developed catalytic systems (i.e., on the base of SiO2). The summarized selectivity towards the glycols formation was found to be ca. 42% at 100% of the cellulose conversion in the presence of Ru@Fe3O4/HPS.